Society participation In Planning Of Minapolitan Area Development (Study In Minapolitan Area Village Sei Ijum Raya District Kotawaringin East) - Vita Maya Nurmarini; Abdul Hakim; Mohammad Rozikin (Wacana Journal of Social and Humanity Studies, 2018)
Fisheries is one of strategic sub-sectors that economically, ecologically, and socio-culture plays an important role in national development. Involvement of fishing communities in various things is needed from planning, organizing, implementing and controlling. Community Development as a concept other than to accommodate participation as well as to increase the capacity of community self-reliance. The purpose of this research is to identify, analyze, describe the development of Minapolitan area of Sei Ijum Raya Village in improving people's welfare, community involvement of Sei Ijum Raya Village in development of minapolitan area based on community development, as well as supporting and inhibiting factors. The research method used is qualitative research method with descriptive approach using qualitative data analysis of interactive model. The findings in the potential field of Sei Ijum Raya Village can support the sustainability of minapolitan area development supported by the local government policy, the mechanism and stages of the planning process in accordance with KEPMEN / RI No.18 of 2011, and encourage participation and involvement of the community in development to achieve optimal benefits for common progress in community development concepts. Supporting factors: Availability of natural resources, increasing perceptions of fishing communities in increasing income, local wisdom of fishing communities. Inhibiting factors: Regional commitment, Human resources, infrastructure.